Glycomics-informed glycoproteomic analysis of site-specific glycosylation for SARS-CoV-2 spike protein - Rosenbalm, Katelyn E. (STAR Protoc, 2020)
This protocol describes an integrated approach for analyzing site-specific N- and O-linked glycosylation of SARS-CoV-2 spike protein by mass spectrometry. Glycoproteomics analyzes intact glycopeptides to examine site-specific microheterogeneity of glycoproteins. Glycomics provides structural characterization on any glycan assignments by glycoproteomics. This procedure can be modified and applied to a variety of N- and/or O-linked glycoproteins. Combined with bioinformatics, the glycomics-informed glycoproteomics may be useful in generating 3D molecular dynamics simulations of certain glycoproteins alone or interacting with one another. For complete details on the use and execution of this protocol, please refer to Zhao et al. (2020).